2012
DOI: 10.1017/s0954579411000800
|View full text |Cite
|
Sign up to set email alerts
|

Sluggish vagal brake reactivity to physical exercise challenge in children with selective mutism

Abstract: Cardiovascular response patterns to laboratory-based social and physical exercise challenges were evaluated in 69 children and adolescents, 20 with selective mutism (SM), to identify possible neurophysiological mechanisms that may mediate the behavioral features of SM. Results suggest that SM is associated with a dampened response of the vagal brake to physical exercise that is manifested as reduced reactivity in heart rate and respiration. Polyvagal theory proposes that the regulation of the vagal brake is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Our results, however, indicate that recently concussed individuals lack control over parasympathetic withdrawal of influence on cardiac rhythm, resulting in a dampened sympathetic response on initiation of exercise. This dampened autonomic response to physical activity has been described in studies of autonomic dysregulation in other clinical populations [16]. …”
Section: Discussionmentioning
confidence: 78%
“…Our results, however, indicate that recently concussed individuals lack control over parasympathetic withdrawal of influence on cardiac rhythm, resulting in a dampened sympathetic response on initiation of exercise. This dampened autonomic response to physical activity has been described in studies of autonomic dysregulation in other clinical populations [16]. …”
Section: Discussionmentioning
confidence: 78%
“…This inability to efficiently remove the vagal brake during challenge has been observed in children, diagnosed with selective mutism, who have difficulty initiating speech. Research characterizes children with selective mutism as having a sluggish vagal brake (Heilman et al, 2012). For CWS, the lack of RSA decrease observed may be a feature consistent with having a sluggish vagal brake, which may in turn influence CWS's ability to effectively and efficiently engage during social-communication situations, a possibility that must await further empirical study.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Bar-Haim et al (2004) found that 7-year-old children who displayed a greater decrease of RSA in response to emotionally and cognitively challenging narrative tasks produced more coherent and adaptive narratives. In addition, decreases of 3- and 4-year-old children's RSA have been reported in response to fear-inducing film stimuli (Gilissen et al, 2007), physical challenge (Heilman et al, 2008), and sustained attention tasks (Suess et al, 1994; Weber et al, 1994). Dale, O'Hara, Keen, and Porges (2011) reported that infants who display less suppression of RSA exhibit more high-level withdrawal responses, including verbal and physical protests, consistent with the relation hypothesized by Porges et al (1996) between physiological regulation of the vagal brake and positive social behavior (see Porges et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suppression of RSA during attention demanding tasks has frequently been used as a psychophysiological index of mental effort and sustained attention (e.g., Vicente, Thornton, & Moray, 1987; Porges, 1992). Several studies have reported dampened RSA reactivity to social and cognitive challenges in children with atypical development including social phobia (Schmitz, Kramer, Tuschen-Caffier, Heinrichs, & Blechert, 2011), fragile X syndrome (Heilman, Harden, Zageris, Berry-Kravis, & Porges, 2011), selective mutism (Heilman et al, 2012), sleep problems (El-Sheikh & Buckhalt, 2004), poor maternal-child relationships (Calkins, Graziano, Berdan, Keane, & Degnan, 2008) , increased risk for obesity (Graziano, Calkins, Keane, & O’Brien, 2011), and lower peer status (Graziano, Keane, & Calkins, 2007). …”
Section: 0 Discussionmentioning
confidence: 99%